Severity of Liver Injury and Its Relation to Clinical Outcome and Duration of Hospitalization in COVID 19 Patients - Cokorde Istri Yuliandari Krisnawardani Kumbara; I Ketut Mariadi; Gde Somayana; I Dewa Nyoman Wibawa; Dwijo Anargha Sindhughosa (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Background: Coronavirus Disease 2019 (COVID-19) can affect not only the respiratory system but also other organs such as the liver. Liver injury tends to occur in severe disease of COVID-19 patients and might contribute to clinical outcomes for patients. This study aimed to find the relationship between the severity of liver injury with clinical outcome and duration of hospitalizations.